An introduction to pensionomics - Mario Arturo Ruiz Estrada; Evangelos Koutronas (Journal of Economics, Finance and Administrative Science, 2020)
Purpose - The purpose of this paper is to explore the concept of pensionomics as a prospective tool for pension evaluation. This paper suggests a paradigm shift - a multi-disciplinary synthesis of differing perspectives in evaluating pension's overall performance based on past work on pension evaluation - incorporating non-economic variables with significant impact on economic growth and social development. Design/methodology/approach - This paper suggests a new analytical tool called "Pensions Consistency (PC) Index" that identifies the level of consistency and the strengths and weaknesses within any pension system. The new conceptual framework focusses on building inter-sectoral and holistic policies able to respond to the new multi-dimensional dynamic environment. Findings - The consideration of pensionomics concept as an evaluation tool for pension schemes provides insights that are helpful in explaining performance differentials. Taking definition, classification and evaluation as a guiding principle, the new conceptual framework can be a useful point of reference for the overall evaluation of pension schemes, revealing deficiencies that traditional evaluation methods cannot detect. The multi-disciplinary approach focusses on building inter-sectoral and holistic policies that are able to respond to the multi-dimensional uncertainties of the new dynamic environment. Research limitations/implications - The heterogeneity and complexity in event dynamics are systemic in the sense that the impact is far from linear. The idiosyncratic nature of unexpected and unpredictable events is rather a result of multi-dimensionality based, among others, on magnitude, frequency, timing, intensity and impact. It is plausible to argue that crisis episodes can destabilize critical systems of economic activity, producing economic spillovers that can directly or indirectly affect the sustainability of pension schemes. If the calculation of direct economic impact is readily traceable, the estimation of indirect economic impact can be an onerous task. Practical implications - Pensionomics places the concept of retirement in a multi-disciplinary context. Pensionomics overcomes theoretical and empirical limitations encountered by the path-dependency perspective, developing a new research agenda to study pension schemes under historical, cultural, social, political, economic, political and environmental prism. Integrating diversified data, techniques, perspectives and concepts, pensionomics' objective is to connect natural and man-made events with social protection mechanisms for the development of a dynamic social protection framework where individual, community and society needs are met effectively and efficiently by implementing tailored policies, closely related to their specific context. Social implications - The concept of retirement has evolved constantly, transforming societies and shaping both income and non-income dimensions of well-being. Pension entitlement turned gradually from a political discourse to a human right discourse. Pension schemes have extended the scope of insurance coverage beyond labour markets and the lifecycle, supporting the broader needs of entire population. Furthermore, pension schemes are widely acknowledged as drivers of economic growth: they enhance labour productivity; foster smooth consumption; and create a stable economic environment for investment and innovation. Current expectations require pension schemes to adopt proactive and reactive policies to examine options for mitigation or for modification of potential consequences in anticipation of exceptional events. Originality/value This paper suggests a paradigm shift, a multi-disciplinary approach called pensionomics, and this "multi-disciplinary" focus builds a new analytical framework to evaluate pension's overall performance based on past work on pension evaluation, incorporating non-economic variables with significant impact on economic growth and social development. PC-Index introduces a comprehensive evaluation tool to study the coverage, performance, efficiency, effectiveness, current trends and future possibilities of pension schemes.
Keywords: E65; 330; Econographicology; Multi-dimensional geometry; Multi-dimensional graphs; Pension systems